Team-based self-directed learning enhanced students’ learning experience in undergraduate surgical teaching. - Sze Kiat, Sim; Myo, Nyunt; Sohail, Mushtaq (Malaysian Medical Association, 2023)
Introduction: To evaluate the effectiveness of team-based self-directed learning (SDL) in the teaching of the undergraduate Year 5 surgical posting.